Characterization of spray-dried kamias (Averrhoa bilimbi) for juice production. - Sebio, Claudine May Ponsica (2018.)
Kamias is an underutilized seasonal fruit of the Philippines which commonly results to waste. Processing it into a powder will lessen its wastage and will make the fruit available year round. Spray drying is one of the best drying techniques ton convert directly the liquid extracts in the powder. This study aimed to produce kamias powder by spray drying from rare-ripe to ripe fruits, to form the kamias juice. Four formulations of kamias juice were made with varying amounts of kamias powder. The most preferred formulation of kamias juice was composed of 15 g kamias powder and 15 g white sugar in 100mL water. A 9-point hedonic scale established the general acceptability of the most preferred kamias juice as ?like much?. The sweetened kamias powder was found to contained 2.71% moisture content and 0.43% crude ash content, both in dry basis. The yeast and mold count was 7.0x102 CFU/g and was within the Gulf Standards. The solubility with water was high with a percentage of 98.88%. Therefore, kamias powder from spray drying can be utilized for juice production. Storage analysis of the kamias powder is recommended. The over-all optimization of processing kamias fruits including identification of degree of maturity is being proposed.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Kamias; Averrhoa bilimbi; Kamias juice production